Lack of Association between Recurrent Pregnancy Loss and Inherited Thrombophilia in a Group of Colombian Patients (2012)
ABSTRACT: Pregnancy is an acquired hypercoagulable state and women with a prior tendency to thrombosis may develop clinical symptoms of placental vascular complications such as preeclampsia, intrauterine growth restriction, and fetal death for unknown causes, that impact the maternal-fetal morbidity and mortality [1–4]. Recurrent pregnancy loss is an important obstetric complication with a prevalence of 1–5% [5]. Inherited thrombophilia has been postulated as cause of recurrent pregnancy loss, although the association between inherited thrombophilia and recurrent pregnancy loss has not been conclusively established. Some studies have demonstrated an association between recurrent pregnancy loss and prothrombotic states rendered by some genetic single nucleotide polymorphisms (SNPs), such as factor V Leiden G1691A (FV Leiden), prothrombin G20210A (FIIG20210A), and methylenetetrahydrofolate reductase C677T (MTHFR C677T), and activated protein C resistance (APC resistance) [6–14], whereas others have reported lack of any association [15–19]. In addition, a retrospective cohort study showed that women with deficiencies of antithrombin (AT), protein C (PC), or protein S (PS) have an eightfold increased relative risk of thrombosis during pregnancy compared to controls [20]. Most of the studies on thrombophilia and recurrent pregnancy loss have been conducted in Caucasian populations [21, 22]. Therefore, the association between these thrombophilias and recurrent pregnancy loss is almost unknown in triethnic populations such as the Colombian population whose genetic mixture is approximately 70% Caucasian, 15% Amerindian, and 15% African [23, 24]. We conducted this study to evaluate the association between inherited thrombophilia and recurrent pregnancy loss in a group of patients from Colombia.